Endophytic Luteibacter yeojuensis strains stimulate banana plant growth - Maria Angel Cruz; Carolyn Alcasid; Mark Angelo Balendres (Advances in Horticultural Science)
This study isolated endophytic bacteria from tissue-cultured banana ultivars Grand Nain and Saba. The bacteria were further characterized and identified through morphological, cultural, and molecular analyses. The bacteria had morphological and colony characteristics resembling those of Luteibacter species. Colonies were white to yellow, round, and slightly raised, with the entire margin in nutrient agar medium. The bacterial isolates were Gram-negative based on the potassium hydroxide test (KOH) test. Phylogenetic analysis of the 16S ribosomal gene region grouped the three isolates in the Luteibacter yeojuensis clade. The three Luteibacter yeojuensis isolates were not pathogenic to banana ‘Grand Nain,’ ‘Lakatan,’ and ‘Saba’ in both wounded and unwounded assays conducted in controlled assays. No stunting, wilting, and corm tissue browning were observed 14 days post-inoculation when the bacteria were inoculated on tissue-cultured plants; two of the three isolates significantly increased plant height of cv. Lakatan (p<0.05) and one isolate, L. yeojuensis GN11-20, enhanced shoot proliferation in cv. Grand Nain. The study reports L. yeojuensis as an endophytic bacterium with growth-promoting activity in tissue-cultured banana plants. The endosymbiotic association of L. yeojuensis in bananas could enhance plant growth and resistance to banana diseases.